Multirate Vibration Attenuation Beyond Nyquist Frequency with Performance, Stability and Robustness Analysis - Sun, Liting; Tomizuka, Masayoshi (IFAC-PapersOnLine, 2017)
In digital/sampled-data motion control systems, the system outputs are only available at certain rates. This sets a great challenge to high-precision motion control systems that subject to high-frequency disturbances, since the feedback regulator cannot directly observe the inter-sample outputs. To handle such situations, a robust multirate control approach is proposed in this paper to enhance disturbance attenuation at high frequencies, including those, under certain conditions, near and beyond the Nyquist Frequency. First, based on the Youla parameterization of all stabilizing controllers, an add-on compensator based on multirate observer is constructed using the a priori nominal model of the disturbance dynamics. Then robust design of a proper Q filter is formulated via the theory of multiple-input-multiple-output (MIMO) robust control, which guarantees the closed-loop stability in the presence of norm-bounded model uncertainties. Effectiveness of the proposed algorithm is evaluated by simulations on a hard disk drive (HDD) benchmark problem, where the inter-sample position errors are approximately recovered and high-frequency disturbance is greatly attenuated with guaranteed closed-loop stability.